Antibiotic Resistance Can Be Enhanced in Gram-Positive Species by Some Biocidal Agents Used for Disinfection - Kampf, Günter (Antibiotics (Basel), 2019)
Some biocidal agents used for disinfection have been described to enhance antibiotic resistance in Gram-negative species. The aim of this review was therefore to evaluate the effect of 13 biocidal agents at sublethal concentrations on antibiotic resistance in Gram-positive species. A MEDLINE search was performed for each biocidal agent on antibiotic tolerance, antibiotic resistance, horizontal gene transfer, and efflux pump. Most data were reported with food-associated bacterial species. In cells adapted to benzalkonium chloride, a new resistance was most frequently found to ampicillin (seven species), cefotaxime and sulfamethoxazole (six species each), and ceftazidime (five species), some of them with relevance for healthcare-associated infections such as Enterococcus faecium and Enterococcus faecalis. With chlorhexidine, a new resistance was often found to imipenem (ten species) as well as cefotaxime, ceftazidime, and tetracycline (seven species each). Cross-resistance was also found with triclosan and ceftazidime (eight species), whereas it was very uncommon for didecyldimethylammonium chloride or hydrogen peroxide. No cross-resistance to antibiotics has been described after low level exposure to glutaraldehyde, ethanol, propanol, peracetic acid, octenidine, povidone iodine, sodium hypochlorite, and polyhexanide. Preference should be given to disinfectant formulations based on biocidal agents with a low or no selection pressure potential.